Strategies to Improve Inpatients’ Quality of Bowel Preparation for Colonoscopy: A Systematic Review and Meta-Analysis - Paraskevas Gkolfakis; Georgios Tziatzios; Ioannis S. Papanikolaou; Konstantinos Triantafyllou (Gastroenterology Research and Practice)
Background and Aims. Inpatients’ bowel preparation before colonoscopy is frequently inadequate, and various interventions have been investigated to improve it, so far. We aimed to evaluate the efficacy of various interventions to improve inpatients’ colon preparation quality. Methods. We systematically reviewed the literature for publications on interventions aiming to improve the quality of inpatients’ colon preparation until June, 2018. Significant heterogeneity—measured with I2—was detected at the level of P<0.1. Adequacy rates were measured using inverse variance, and the size effect of different interventions was calculated using random effects model and expressed as odds ratio (OR). Results. Seventeen studies enrolling 2733 inpatients were included. Overall, 67% (60-75%) of the participants achieved adequate colon cleansing (I2=97%; P<0.001). In six studies assessing the impact of educational interventions to patient/physician/nurse vs. no intervention, adequate bowel preparation was achieved in 77% (62-91%) vs. 50% (32-68%) of the patients (OR 95%CI=3.49 (1.67-7.28), P=0.0009; I2=74%; P=0.002). Ten studies examined variations (qualitative and/or quantitative) in bowel preparation regimens with adequate preparation detected in 71% (60-81%) of the participants, and a single study examined the administration of preparation through an esophagogastroduodenoscope, resulting in adequate prep in 71% of the patients. Conclusions. Despite several interventions, only two-thirds of inpatients achieve adequate colon preparation before colonoscopy. Educational interventions significantly improve inpatients’ bowel preparation quality.